The Convergence of Alpha-Synuclein, Mitochondrial, and Lysosomal Pathways in Vulnerability of Midbrain Dopaminergic Neurons in Parkinson’s Disease - Minakaki, Georgia; Krainc, Dimitri; Burbulla, Lena F. (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is the second most common neurodegenerative disease, characterized by progressive bradykinesia, rigidity, resting tremor and gait impairment, as well as a spectrum of non-motor symptoms including autonomic and cognitive dysfunction. The cardinal motor symptoms of PD stem from the loss of substantia nigra (SN) dopaminergic neurons, and it remains unclear why SN dopaminergic neurons are preferentially lost in PD. However, recent identification of several genetic PD forms suggests that mitochondrial and lysosomal dysfunction play an important role in the degeneration of midbrain dopamine neurons. In this review, we discuss the interplay of cell-autonomous mechanisms linked to dopaminergic neuron vulnerability and alpha-synuclein homeostasis. Emerging studies highlight a deleterious feedback cycle, with oxidative stress, altered dopamine metabolism, dysfunctional lysosomes, and pathological alpha-synuclein species representing key events in the pathogenesis of PD. We also discuss the interactions of alpha-synuclein with toxic dopamine metabolites, as well as the biochemical links between intracellular iron, calcium and alpha-synuclein accumulation. We suggest that targeting multiple pathways, rather than individual processes, will be important for developing disease-modifying therapies. In this context, we focus on current translational efforts specifically targeting lysosomal function, as well as oxidative stress via calcium and iron modulation. These efforts could have therapeutic benefits for the broader population of sporadic PD, and related synucleinopathies.